Aptitud de las secretarias para la buena comunicación de relaciones interpersonales en el área de secretaria de la Unidad Educativa 11 de Octubre - Moyano Limones, Nally Narcisa (2022)
The current case study based on the theme of the secretaries' aptitude for good communication of interpersonal relationships in the secretarial area of the educational unit October 11, whose objective was to analyze the aptitude of the secretaries to have a better communication, in reference to the interpersonal relationship. The study carried out used a descriptive and field research methodology, which identified the aspects and factors of the secretaries' aptitude and thus analyze the good communication in interpersonal relationships in the secretaries, the type of quantitative research to obtain accurate data in reference to the data, has been used in situation to the objective of the study to seek solution to the problem posed that help to improve the secretaries' aptitude and interpersonal relationship. The research instrument used for this case study is based on a survey which allowed us to obtain the information for the conclusion of the case study. In conclusion, certain shortcomings and deficiencies have been evidenced based on the aptitude of each secretary, it has been identified that several secretaries of the educational unit do not have a good understanding of the users and that they do not have good communication within the work area.